2006
DOI: 10.1111/j.1600-051x.2006.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Compromised GCF total antioxidant capacity in periodontitis: cause or effect?

Abstract: Local total antioxidant capacity in CP appears to reflect increased oxygen radical activity during periodontal inflammation and can be restored to control subject levels by successful non-surgical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
169
7
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(195 citation statements)
references
References 44 publications
11
169
7
8
Order By: Relevance
“…In the present study, lower GPx activity in chronic periodontitis group is observed than in controls. Similar findings were reported by studies [26,32]. Guentsch et al [36] have showed that periodontally healthy subjects demonstrated significantly lower levels of GP x than the periodontitis group including smokers.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, lower GPx activity in chronic periodontitis group is observed than in controls. Similar findings were reported by studies [26,32]. Guentsch et al [36] have showed that periodontally healthy subjects demonstrated significantly lower levels of GP x than the periodontitis group including smokers.…”
Section: Discussionsupporting
confidence: 82%
“…Various studies have associated periodontitis with compromised antioxidant activities. Studies [26,27] have reported lower TAOC in saliva, gingival blood and peripheral blood of subjects with chronic periodontitis as compared to healthy control group as observed in our study. Al Bayaty et al [28] has observed lowered antioxidant in smokers as compared to non-smokers.…”
Section: Discussionsupporting
confidence: 69%
“…Elde ettiğimiz klinik parametrelerle çalışmamıza benzer nitelikteki araştırmaların bulguları desteklenmiştir. 17 Literatürdeki plazma TAOK seviyelerinin değerlendirildiği çalışmalarda, bulgularımızla benzer olarak, periodontitisli bireylerin plazma TAOK seviyelerinin anlamlı oranda düşük olduğu belirtilmektedir. 9,17 Tükürük TAOK seviyesi değerlendirildiğinde ise, tartışmalı çalışma sonuçları karşımıza çıkmaktadır.…”
Section: şEkil 1 Taok Tükürük Değerlerinin Gruplar Arası Karşılaştırunclassified
“…9 Benzer şekilde, Chapple ve ark, periodontal hastalıklı bireylerin plazma TAOK seviyelerinin, sağlıklı bireylere oranla anlamlı derecede düşük olduğunu bulmuştur. 17 Bulgularımızdan farklı olarak tükürük TAOK değerlerinin periodontitisli bireylerde anlamlı oranda düşük olduğunu bildiren çalışmalar da bulunmaktadır. 14,15,25 Sculley ve ark, CPITN indeksi ile periodontal hastalık şiddetini belirlediği çalışmala-rında, periodontal hastalığın şiddeti arttıkça tükürük TAOK seviyesinin anlamlı oranda azaldığını bulmuştur.…”
Section: şEkil 1 Taok Tükürük Değerlerinin Gruplar Arası Karşılaştırunclassified
“…Total antioxidant capacity levels were found to be significantly lower in CP patients when compared with healthy controls, although the mechanism responsible for oral AO decrease in CP has yet to be investigated. 7,8 Nonetheless, adjuvant AO therapy for CP has a potential to improve periodontal clinical parameters. 9,10 Nuclear factor erythroid 2-related factor 2 (Nrf2) regulates gene transcription of a large group of antioxidant and phase 2 detoxifying enzymes playing a central role in cellular defense against oxidative and electrophilic insults.…”
mentioning
confidence: 99%